Deformidades angulares em muares: diagnóstico e tratamento - Bruno Zambelli Loiacono (2010)
The objective was to diagnose, treat and monitor an outbreak of angular limb deformity (ALD) in a herd of mules. Members were treated according to the deviation. Members with deviation 3 ° were subjected to trimming correction (TC); deviations > 3 ° and 7° were treated with transection and elevation of the periosteum and trimmed (TEP), deviations> 7 ° were subjected to the same measures adopted in the group TEP associated with the trans-physeal staple (GTF). The variations of ALD were evaluated on radiographs obtained 45 days before (T0), at baseline (T1) and 30 (T2) and 60 (T3) after establishment of the treatment. In T1, T2 and T3, were performed routine examination of synovial fluid (SF) and determination of nitrite concentration (Ni). The incidence of ALD (37.1%) was attributed to the trainning protocol established and was less significant than those described in horses. Between T0 and T1 there was no variation of the ALD. In the TEP group, the reduction starting from T2 was similar to those reported in horses, but it occurred in less time and in elder mules. In the GTF group, the ALD reduced only in T3, probably due to the advanced age of the group. In SF was detected a reduced concentration of Ni, although it was within the reference patterns. It is concluded that the exercise protocol resulted in the occurrence of ALD in mules. The treatment in the TEP group, was able to reduce the ALD, despite the age of the mules. The intensity of the ALD was not able to result in changes in SF